The Eastern Shore - Just, Ward S. (Houghton Mifflin Harcourt, 2016)
"From an American master comes another "beautifully languid, emotionally intense tale" (Entertainment Weekly), this time of a newspaper editor's fateful decision to expose a small-town fugitive. Ned Ayres, the son of a judge in an Indiana town in midcentury America, has never wanted anything but a newspaper career--in his father's appalled view, a "junk business," a way of avoiding responsibility. The defining moment comes early, when Ned is city editor of his hometown paper. One of his beat reporters fields a tip: William Grant, the town haberdasher, married to the bank president's daughter and father of two children, once served six years in Joliet. The story runs--Ned offers no resistance to his publisher's argument that the public has a right to know. The consequences, swift and shocking, haunt him throughout a long career, as he moves first to Chicago, where he engages in a spirited love affair that cannot, in the end, compete with the pull of the newsroom--"never lonely, especially when it was empty"--And the "subtle beauty" of the front page. Finally, as the editor of a major newspaper in post-Kennedy-era Washington, DC, Ned has reason to return to the question of privacy and its many violations--the gorgeously limned themes running through Ward Just's elegiac and masterly new novel"--